Intrinsic versus Extrinsic Motivation in Online Learning: A Self-Determination Theory Approach - Desma Husni (Global Perspectives in Education Journal, 2026)
This study aimed to examine the roles of intrinsic and extrinsic motivation in shaping students’ engagement and academic performance in online learning environments, using Self-Determination Theory as the guiding framework. The research was conducted in August 2025 at the Institut Agama Islam Negeri SUSKA, Indonesia, involving 98 third-semester students enrolled in online coursework. A quantitative correlational design was employed, utilizing the Intrinsic Motivation Inventory (IMI) and the Academic Motivation Scale (AMS) to measure students’ intrinsic and extrinsic motivation levels. Online learning performance was assessed through official course grades obtained from the academic department. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The results showed that intrinsic motivation was positively and significantly associated with online learning performance, whereas extrinsic motivation demonstrated a weaker but still meaningful relationship with students’ engagement. Regression findings indicated that intrinsic motivation emerged as the strongest predictor of online learning outcomes. These findings underscore the importance of creating autonomy-supportive digital learning environments that foster students’ internal motivational processes.